2019
DOI: 10.1177/0003702819828809
|View full text |Cite
|
Sign up to set email alerts
|

Online Characterization of Single Airborne Carbon Nanotube Particles Using Optical Trapping Raman Spectroscopy

Abstract: Carbon nanotubes (CNTs) have become recognized as a potential environmental and health hazard as their applications are broadening and manufacturing costs are reducing. Fundamental information of CNTs in air is of significant importance to our understanding of their environmental fate as well as to further applications. Extensive efforts have been made over decades on characterizing CNTs; however, a majority of the studies are of bulk or CNTs dispersed on substrates. In the present study, we characterize singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The Raman spectra in (ii)-(B) was interfered by the background fluorescence of the impurities that were assigned to the clay components by the additional Raman peak at 3087 cm −1 . Well-resolved clear Raman D and G bands of carbon were also reported later in carbon nanotubes trapped in air using different opticaltrapping configurations, such as a standing-wave trap [171], an annular laser beam trap [172], and a UOT [68].…”
Section: Figuresupporting
confidence: 53%
See 1 more Smart Citation
“…The Raman spectra in (ii)-(B) was interfered by the background fluorescence of the impurities that were assigned to the clay components by the additional Raman peak at 3087 cm −1 . Well-resolved clear Raman D and G bands of carbon were also reported later in carbon nanotubes trapped in air using different opticaltrapping configurations, such as a standing-wave trap [171], an annular laser beam trap [172], and a UOT [68].…”
Section: Figuresupporting
confidence: 53%
“…A recent work introduces a confocal-beam trap that is formed by one forward hollow beam and its reflected backward hollow beam [66]. More recently, Gong et al have demonstrated a universal optical trap (UOT) using two horizontally counter-propagating hollow beams [54,67,68], which can trap single particles of arbitrary properties, ranging from transparent to absorbing, from inorganic/organic to biological, from solids to droplets, from spherical to irregularly shaped particles, or from sub-micron to ∼50 µm in size. In 2019, the UOT design was further advanced by Pan et al using two parabolic reflectors and a hollow laser beam, and higher trapping efficiency and stronger trapping robustness was realized [69].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in vibrational spectroscopic techniques offer potential for measuring airborne pollutants. An innovative optical-trapping Raman method examined 53 single suspended CNTs, an approach that eliminates measurement artifacts arising from sampling onto filters. A Raman method for the analysis of respirable crystalline silica (RCS) collected on silver filters had 54 a LOD of 0.26 μg, which was an order of magnitude better than that achievable by established XRD and FTIR approaches.…”
Section: Air Analysismentioning
confidence: 99%
“…Touch-free and charge-free OT techniques have been advanced to trap diverse types of airborne particles in recent years (Gong et al 2018a). With a single particle isolated and trapped in air, Raman spectroscopy was utilized to study single droplets (Kalume et al 2017), mineral dust surrogates (Rkiouak et al 2014), pharmaceutical aerosols (Gallimore et al 2018), and carbonaceous particles (Uraoka, Maegawa, and Ishizaka 2017;Gong et al 2019). Raman spectra from an optically trapped bioaerosol, however, were obtained only very recently (Wang et al 2015;Gong et al 2018b).…”
Section: Introductionmentioning
confidence: 99%